2022
DOI: 10.1021/acsomega.2c00987
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Two-Phase Explosion Suppression of Gas/Pulverized Coal by Explosion Suppressant

Abstract: Pulverized coal is widely distributed in coal mine roadways, which can enhance the power of a gas explosion. Explosion suppression technology can effectively reduce the explosion power. At present, rock powder shed, a water bag, and ABC powder are widely used in most coal mine explosion suppression technologies. In order to verify the explosion suppression effect of rock powder, water, and ABC powder in the pulverized coal environment, a series of experiments on a suppressing gas/pulverized coal two-phase expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Li 16 investigated the reasons and mechanism of CD rising induced by gas explosion shock waves by performing experiments in a large roadway. According to the leading role of the ignition mechanism of different CD clouds in the explosion process, Liu and Si 17 divided the combustion mode into deposited CD lifting explosion and deposited CD flame combustion. When it comes to numerical simulation research, Liu et al 18 used the continuous-phase and particle-phase calculation methods to numerically simulate the propagation process of deposited CD explosions induced by gas explosions.…”
Section: Related Scholars Have Conducted Extensive Physical Experimentsmentioning
confidence: 99%
“…Li 16 investigated the reasons and mechanism of CD rising induced by gas explosion shock waves by performing experiments in a large roadway. According to the leading role of the ignition mechanism of different CD clouds in the explosion process, Liu and Si 17 divided the combustion mode into deposited CD lifting explosion and deposited CD flame combustion. When it comes to numerical simulation research, Liu et al 18 used the continuous-phase and particle-phase calculation methods to numerically simulate the propagation process of deposited CD explosions induced by gas explosions.…”
Section: Related Scholars Have Conducted Extensive Physical Experimentsmentioning
confidence: 99%
“…Passive explosion suppression technology is primarily accomplished by dispersing explosive suppression powder or absorbing materials to reduce the intensity of explosion flames and shock waves. Through experiments, Liu et al [ 3 ] investigated the effects of rock powder, water, and ABC dry powder on suppressing explosions. The findings revealed that while water and rock powder effectively suppressed shock waves and the Hull explosion flame of coal powder secondary explosion, ABC dry powder had the most effective overall suppressive effect.…”
Section: Introductionmentioning
confidence: 99%
“…Coal dust explosion is a major disaster accident in the mine, and the formation of flame is one of the main characteristics during the long-distance propagation of shock waves [1,2]. The average theoretical pressure of a coal dust explosion in a mine is 736 KPa [3], and overpressure leads to the raising of dust fall in the roadway and the formation of new coal dust by breaking up the coal body, which poses a major hazard in coal mines [4][5]. Coal dust explosions require sufficient ignition energy and the ignition delay time has a significant impact on whether an explosion occurs and the propagation characteristics of the explosion flame [6,7].…”
Section: Introductionmentioning
confidence: 99%